Perencanaan Strategis Sistem Informasi Menggunakan Metode Ward and Peppard (Studi Kasus: Dinas Pariwisata Kabupaten Timor Tengah Selatan) - Dennis Christian Tallo; Frederik Samuel Papilaya (Journal of Information System and Informatics, 2021)
The Timor Tengah Selatan Regency Tourism Office is one of the regional apparatus organizations that has the authority to implement the regional government's authority in the tourism sector. Information Technology Systems are factors that affect the sustainability of organization's activities. The Timor Tengah Selatan Regency Tourism Office still encounters obstacles in the application of information systems that do not support the entire business process and the lack of IS implementation makes performance inefficient. One of the contributing factors is that there are not enough human resources who have the skills in managing information systems and information technology properly. The purpose of this research is to develop a strategic planning of information systems in accordance with the needs of the organization. In the preparation of information systems strategic planning research using the Ward and Peppard approach with various analyzes such as SWOT analysis, Value Chain, and Mc. Farlan Strategic Grid. Based on the results of this study resulted in several recommendations to be carried out including the creation of Contract Making Administration System, and Mobile Tourism Information System and the development of Regency Tourism Website Timor Tengah Selatan regency, SIPD (Local Government Information System), and SIMDA (Regional Management Information System) GOODS.